Management of atrophic mandibular fractures: An Italian multicentric retrospective study. Issue 12 (December 2018) - Gerbino, Giovanni; Cocis, Stefan; Roccia, Fabio; Novelli, Giorgio; Canzi, Gabriele; Sozzi, Davide
Abstract: Purpose: The aim of this multicentric study was to retrospectively evaluate the surgical outcome of atrophic mandible fractures treated with open reduction and rigid fixation (ORIF), using load-bearing plates. Materials and methods: 55 patients from three trauma centers were retrieved for the study. Inclusion criteria were: edentulous patients with mandibular body fractures; mandibular body thickness <20 mm. Collected data included: cause of fracture; degree of atrophy (according to Luhr's classification); characteristics of the fracture; adequacy of reduction; postoperative complications. All patients were treated with ORIF, using 2.0 mm, large-profile, locking bone plates and 2.4 mm locking bone plates. No bone graft was used in any case. Results: 12 patients were classified as class I atrophy, 18 patients as class II, and 25 patients as class III. Mean mandibular height at the site of fracture was 12.8 mm (ranging from 5.4 mm to 20 mm). 22 were unilateral fractures and 23 were bilateral. Mild displacement was observed in 11 fractures, moderate in 34, severe in 16, and comminution was present in seven fractures. Adequacy of reduction was judged good in 62 fractures and poor in six fractures. Transient weakness of the marginal branch of the facial nerve was recorded in 11 patients and permanent weakness in two patients. All patients achieved a complete fracture healing. Conclusion: External open reduction and rigid fixation (ORIF) with locking, load-bearing plates is a reliable and predictable treatment for atrophic edentulous mandible fracture. Immediate bone grafting should not be considered mandatory unless there is consistent bone loss.